The Role of Religious Leaders in Conflict Transformation - Bodenbender, Stanislava; Maslowski, Nicolas, 1972-; Kratochvíl, Petr, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
Religion has often been viewed as a source of conflict and violence in international relations. Yet history provides that religion has also been a source and inspiration for peace building and non-violent resistance. The role of religious leaders in conflict transformation has been treated as a marginal phenomenon. Appleby (2000) points out that identifying and documenting the roles of religious actors in resolving protracted conflicts remains an unfinished task. This thesis is an attempt to meet such challenge by focusing on religious leaders and their role in search of solutions in deeply rooted conflicts. Working from the premise that religious leaders can make a substantial contribution in conflict transformation, the overarching goal of this thesis is to examine what roles religious actors play and how equipped they are to serve their communities in their capacity as peacemakers.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses